2014
DOI: 10.1088/0957-4484/25/49/495606
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared bioluminescence resonance energy transfer from firefly luciferase—quantum dot bionanoconjugates

Abstract: The bioluminescence resonance energy transfer (BRET) between firefly luciferase enzymes and semiconductive quantum dots (QDs) with near infrared emission is described. The QD were phase transferred to aqueous buffers using a histidine mediated phase transfer route, and incubated with a hexahistidine tagged, green emitting variant of firefly luciferase from Photinus pyralis (PPyGRTS). The PPyGRTS were bound to the QD interface via the hexahistidine tag, which effectively displaces the histidine layer and binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…20,21 In practice, bioluminescing proteins such as Renilla reniformis luciferase (Luc) are attached to the QDs where their oxidation of a chemical substrate produces either localized light emission or an exciton that can sensitize the QD. 29,30 More pertinently, they showed that attaching red-shifted fluorescent proteins to the QDs could give rise to a multistep BRET-FRET process; this served as an important confirmation from which we would build upon. [21][22][23][24] Quinones et al extended this QD assay format to quantitatively probe cellular surface-and proteinprotein interactions in a manner that was far more sensitive than conventional direct fluorescence-based approaches.…”
Section: Introductionmentioning
confidence: 70%
“…20,21 In practice, bioluminescing proteins such as Renilla reniformis luciferase (Luc) are attached to the QDs where their oxidation of a chemical substrate produces either localized light emission or an exciton that can sensitize the QD. 29,30 More pertinently, they showed that attaching red-shifted fluorescent proteins to the QDs could give rise to a multistep BRET-FRET process; this served as an important confirmation from which we would build upon. [21][22][23][24] Quinones et al extended this QD assay format to quantitatively probe cellular surface-and proteinprotein interactions in a manner that was far more sensitive than conventional direct fluorescence-based approaches.…”
Section: Introductionmentioning
confidence: 70%
“…The incorporation of luciferase-encoding plasmids into bacteria is a common approach for the development of bioluminescent reporter strains (26). Chromosomally integrated luciferases are often preferred (27), because they are more stable than plasmid-based reporters, although sensitivity is generally lower (17,28). It is recognized that plasmid-based reporters may be unstable in vivo in the absence of antibiotic selection (23,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to the development of optimized BRET efficiency, the sophistication of such systems has steadily grown by integrating other elements, such as organic fluorophores [57] or FPs [58] to the existing constructs. They can work in concert with the QD to harvest luciferase light energy and utilize it by spatially and spectrally propagating it in a unique fashion that can potentially broaden their breadth of application.…”
Section: Bret-multistep Fret Constructsmentioning
confidence: 99%